A comprehensive evaluation of catalase-like activity of different classes of redox-active therapeutics - Tovmasyan, Artak; Maia, Clarissa G.C.; Weitner, Tin; Carballal, Sebastián; Sampaio, Romulo S.; Lieb, Dominik; Ghazaryan, Robert; Ivanovic-Burmazovic, Ivana; Ferrer-Sueta, Gerardo; Radi, Rafael; Reboucas, Julio S.; Spasojevic, Ivan; et al. (Free radical biology & medicine, 2015)
Because of the increased insight into the biological role of hydrogen peroxide (H2O2) under physiological and pathological conditions and the role it presumably plays in the action of natural and synthetic redox-active drugs, there is a need to accurately define the type and magnitude of reactions that may occur with this intriguing and key species of redoxome. Historically, and frequently incorrectly, the impact of catalase-like activity has been assigned to play a major role in the action of many redox-active drugs, mostly SOD mimics and peroxynitrite scavengers, and in particular MnTBAP3– and Mn salen derivatives. The advantage of one redox-active compound over another has often been assigned to the differences in catalase-like activity. Our studies provide substantial evidence that Mn(III) N-alkylpyridylporphyrins couple with H2O2 in actions other than catalase-related. Herein we have assessed the catalase-like activities of different classes of compounds: Mn porphyrins (MnPs), Fe porphyrins (FePs), Mn(III) salen (EUK-8), and Mn(II) cyclic polyamines (SOD-active M40403 and SOD-inactive M40404). Nitroxide (tempol), nitrone (NXY-059), ebselen, and MnCl2, which have not been reported as catalase mimics, were used as negative controls, while catalase enzyme was a positive control. The dismutation of H2O2 to O2 and H2O was followed via measuring oxygen evolved with a Clark oxygen electrode at 25°C. The catalase enzyme was found to have kcat(H2O2)=1.5×106M–1 s–1. The yield of dismutation, i.e., the maximal amount of O2 evolved, was assessed also. The magnitude of the yield reflects an interplay between the kcat(H2O2) and the stability of compounds toward H2O2-driven oxidative degradation, and is thus an accurate measure of the efficacy of a catalyst. The kcat(H2O2) values for 12 cationic Mn(III) N-substituted (alkyl and alkoxyalkyl) pyridylporphyrin-based SOD mimics and Mn(III) N,N′-dialkylimidazolium porphyrin, MnTDE-2-ImP5+, ranged from 23 to 88M–1 s–1. The analogous Fe(III) N-alkylpyridylporphyrins showed ~10-fold higher activity than the corresponding MnPs, but the values of kcat(H2O2) are still ~4 orders of magnitude lower than that of the enzyme. While the kcat(H2O2) values for Fe ethyl and n-octyl analogs were 803.5 and 368.4M–1 s–1, respectively, the FePs are more prone to H2O2-driven oxidative degradation, therefore allowing for similar yields in H2O2 dismutation as analogous MnPs. The kcat(H2O2) values are dependent on the electron deficiency of the metal site as it controls the peroxide binding in the first step of the dismutation process. SOD-like activities depend on electron deficiency of the metal site also, as it controls the first step of O2●− dismutation. In turn, the kcat(O2●−) parallels the kcat(H2O2). Therefore, the electron-rich anionic non-SOD mimic MnTBAP3– has essentially very low catalase-like activity, kcat(H2O2)=5.8M–1 s–1. The catalase-like activities of Mn(III) and Fe(III) porphyrins are at most, 0.0004 and 0.05% of the enzyme activity, respectively. The kcat(H2O2) values of 8.2 and 6.5M–1 s–1 were determined for electron-rich Mn(II) cyclic polyamine-based compounds, M40403 and M40404, respectively. The EUK-8, with modest SOD-like activity, has only slightly higher kcat(H2O2)=13.5M–1 s–1. The biological relevance of kcat(H2O2) of MnTE-2-PyP5+, MnTDE-2-ImP5+, MnTBAP3–, FeTE-2-PyP5+, M40403, M40404, and Mn salen was evaluated in wild-type and peroxidase/catalase-deficient E. coli. [Display omitted] •Catalase-like activity of different classes of redox active compounds, described by kcat(H2O2) and yield of O2 evolution, was assessed.•Mn(III) and Fe(III) porphyrins have catalase-like activity in the range of 0.0004 to 0.05% of the enzyme activity, respectively.•Mn salen EUK-8 has 0.0009% of enzyme activity, while M40403, M40404, and tempol have no detectable catalase-like activity.•Low catalase-like activity of compounds studied must be taken into account when drawing conclusions on their mechanism(s) of action(s) in vitro and in vivo.